ANALISIS IMPLEMENTASI QUALITY CONTROL PADA PRODUKSI GULA PT. PERKEBUNAN NUSANTARA XIV (PERSERO) PABRIK GULA TAKALAR KABUPATE TAKALAR - Jumriani Jumriani; Muh Aris Pasigai; M Hidayat (Universitas Muhammadiyah Makassar, 2019)
JUMRIANI, Year 2018 Analysis of Implementation of Quality Control on Sugar Production in PTP. NUSANTARA XIV (PERSERO) Takalar Sugar Factory Takalar Regency, Thesis Management Study Program, Faculty of Economics and Business, University of Muhammadiyah Makassar. Supervised by Advisor I Moh. Aris Pasigai and Advisor II M. Hidayat. This study aims to determine the implementation in a quality control on sugar production in a state-owned company engaged in the manufacturing industry. The type of research used in the study is descriptive qualitative. The focus of this study includes how to find out the process of forming sugar from raw materials into crystal grains with the help of a quality control system. This research was conducted to improve the quality of production so that companies can still compete competitively. There needs to be an application that can help so that in the production process there are no obstacles or problems, so do the machines used in the production process. More care is needed so that in the production process the quality of sugar can be maintained.